Aspartic protease inhibitor enhances resistance to potato virus Y and A in transgenic potato plants - Zhila Osmani; Mohammad Sadegh Sabet; Kenji S. Nakahara (BMC Plant Biology, 2022)
Abstract Background Viruses are the major threat to commercial potato (Solanum tuberosum) production worldwide. Because viral genomes only encode a small number of proteins, all stages of viral infection rely on interactions between viral proteins and host factors. Previously, we presented a list of the most important candidate genes involved in potato plants’ defense response to viruses that are significantly activated in resistant cultivars. Isolated from this list, Aspartic Protease Inhibitor 5 (API5) is a critical host regulatory component of plant defense responses against pathogens. The purpose of this study is to determine the role of StAPI5 in defense of potato against potato virus Y and potato virus A, as well as its ability to confer virus resistance in a transgenic susceptible cultivar of potato (Desiree). Potato plants were transformed with Agrobacterium tumefaciens via a construct encoding the potato StAPI5 gene under the control of the Cauliflower mosaic virus (CaMV) 35S promoter. Results Transgenic plants overexpressing StAPI5 exhibited comparable virus resistance to non-transgenic control plants, indicating that StAPI5 functions in gene regulation during virus resistance. The endogenous StAPI5 and CaMV 35S promoter regions shared nine transcription factor binding sites. Additionally, the net photosynthetic rate, stomatal conductivity, and maximum photochemical efficiency of photosystem II were significantly higher in virus-infected transgenic plants than in wild-type plants. Conclusion Overall, these findings indicate that StAPI5 may be a viable candidate gene for engineering plant disease resistance to viruses that inhibit disease development.